2016
DOI: 10.1515/aut-2015-0043
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Physical Properties and Hand of Jean Fabric

Abstract: We investigated the distinctive characteristics of jean fabrics (denim fabrics obtained from jeans) and compared the physical properties and the hand. We used 13 kinds of jean fabric from commercial jeans and 26 other fabric types. The physical properties were measured using the Kawabata evaluation system, and the fabric hand was evaluated by 20 subjects using a semantic differential method. To characterise the hand of jean fabrics compared with other fabrics, we used principal component analysis and obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Kawamura et al [24] studied the handle of jean fabrics from different countries and manufacturers. Their research showed that the jeans fabrics produced in the United States were rough and hard, but the Japanese fabrics were soft and smooth.…”
Section: Methodsmentioning
confidence: 99%
“…Kawamura et al [24] studied the handle of jean fabrics from different countries and manufacturers. Their research showed that the jeans fabrics produced in the United States were rough and hard, but the Japanese fabrics were soft and smooth.…”
Section: Methodsmentioning
confidence: 99%
“…In the research of women's vests, the style design elements which have great influences on users' perception are extracted, and the association model between users' perception and style design features is established (Chen and Cheng, 2019). In the study of denim fabrics, the association between physical properties of fabrics and users' subjective hand feel is explained (Kawamura et al , 2016). Kim (Kim et al , 2020) investigated a suitable position for the bustline of the upper garment.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers use quantitative methods such as quantitative class I theory (Kawamura et al , 2016), principal component analysis and multiple linear regression analysis to establish regression models to identify the relationship between certain design elements and users' perception. In the research of women's vests, the style design elements which have great influences on users' perception are extracted, and the association model between users' perception and style design features is established (Chen and Cheng, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Shaker исследовано влияние структуры переплетения и плотности нити на эксплуатационные и механические свойства тканей [2]. В работе A. Kawamura, C. Zhu, J. Peiffer исследованы особенности и свойства джинсовых тканей [3]. В работе R. Halfaoui, B. Chemani приведены исследования изменений в физических характеристик пряжи в результате механических усилий, которым они подвергаются на ткацком станке [4].…”
Section: Introductionunclassified